2011
DOI: 10.1021/ma201165y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Borderline Solvents to Induce Pronounced Extended-Chain Lamellar Order in π-Stackable Polymers

Abstract: Thin films of poly[2,5-bis(3-tetradecylthiophen-2-yl)thieno[3,2-b]thiophene] (C14–PBTTT) exhibit a monolayer-terraced morphology that indicates a pronounced lamellar order with π-stacks of extended polymer chains. Previously this remarkable state of order was thought to be promoted by the interdigitation of alkyl side chains between the lamellae during cooling from the liquid-crystalline (LC) phase. Here we establish that the key to this ordering in fact is the formation of unentangled π-stacks of extended pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 46 publications
8
52
0
Order By: Relevance
“…Utilizing single molecule spectroscopy (SMS), Hu et al also reported that with the gradually more intense conjugation in chains brought by a better planarity (for PQT12, P3), highly delocalized thienothiophene fused aromatic rings (for pBTTT) and a much higher planarity due to intra-chain donor-acceptor charge transfer (for pTzQT, P8) compared than P3HT, the content of single chains with an extended conformation in solutions increased, which suggested a more ordered and aligned rod-like film morphology arising from these rod-like single chains [109]. Thus, it is proven that the conformations of conjugated polymers display more anisotropic and extended characteristics as a result of planarity and rigidity [68,69,109], which have an important effect on the self-assembly and film morphology in terms of the stacking order.…”
Section: The Effect Of Planarity and Rigidity On Structure Morphologmentioning
confidence: 99%
See 4 more Smart Citations
“…Utilizing single molecule spectroscopy (SMS), Hu et al also reported that with the gradually more intense conjugation in chains brought by a better planarity (for PQT12, P3), highly delocalized thienothiophene fused aromatic rings (for pBTTT) and a much higher planarity due to intra-chain donor-acceptor charge transfer (for pTzQT, P8) compared than P3HT, the content of single chains with an extended conformation in solutions increased, which suggested a more ordered and aligned rod-like film morphology arising from these rod-like single chains [109]. Thus, it is proven that the conformations of conjugated polymers display more anisotropic and extended characteristics as a result of planarity and rigidity [68,69,109], which have an important effect on the self-assembly and film morphology in terms of the stacking order.…”
Section: The Effect Of Planarity and Rigidity On Structure Morphologmentioning
confidence: 99%
“…It is known that a polymer chain could be regarded as its equivalent Kuhn chains, in which the motion units are modeled as Kuhn segments made of several repeating units [68,69]. Due to the large bending barrier of stiff conjugated polymers, the Gaussian chain model fitting well with flexible chains [Equation (2)] is replaced by worm-like chain model [Equation (3)] to better depict the conformation of rigid conjugated polymers,…”
Section: Structural Differences Between Conjugated Polymers and Fleximentioning
confidence: 99%
See 3 more Smart Citations